Why do authoritarian regimes adopt bicameralism? Cooptation, control, and masking controversial reforms. Issue 5 (4th July 2018) - Baturo, Alexander; Elgie, Robert
ABSTRACT: The adoption of bicameralism in the world is increasingly an authoritarian phenomenon: while the percentage of bicameral democracies is in decline, there has been a steady increase in bicameral non-democracies. What makes non-democracies turn to bicameralism? We argue that bicameralism may serve as a means of post-conflict reconciliation or control of the legislature when the opposition gains seats in the lower chamber. We also propose a novel explanation whereby the introduction of bicameralism helps to mask a set of more controversial constitutional reforms. Drawing on a new dataset on second chambers from 1945 to 2016, we find that bicameralism is more likely to be adopted during years when formal presidential term limits are in place or when leaders are in their last term. This is because bicameralism is often a by-product of broad institutional reform that assists in justifying and legitimating the need for constitutional revision and in masking the extension of presidential term limits. The findings improve our understanding of institutions and institutional origins in dictatorships.